The Guilty Brelfie: Censored Breastfeeding Selfies Reclaim Public Space. Issue 1 (1st June 2019) - Ramler, Mari E.
Abstract : Breastfeeding mothers and their babies are simultaneously in the public sphere and hidden from public view. Although social media has the potential to normalize attitudes toward breastfeeding by increasing visibility, Facebook and Instagram maintain an unpredictable censorship policy toward "brelfies"—female breast selfies—which has undermined progress. Combining Iris Marion Young's "undecidability" of the breasted experience with Brett Lunceford's rhetoric of nakedness, this article investigates what breastfeeding mothers communicate online via digital images when they expose their breasts. By deconstructing controversial case studies, this article concludes that brelfies have increased breastfeeding's accessibility and acceptability in the material world.